A network perspective of knowledge transfer in tourism. (January 2020) - Raisi, Hossein; Baggio, Rodolfo; Barratt-Pugh, Llandis; Willson, Gregory
Abstract: Efficient transfer of knowledge is the prerequisite for innovation and competitiveness of tourism destinations. This paper uses network analysis to examine inter-organizational knowledge transfer in Western Australian tourism. The findings indicate that Western Australian network has low connectivity and is highly centralized around public bodies with a hierarchical pattern. The network also exhibits few reciprocal relationships with limited boundary spanners. The findings improve the understanding of the Western Australian tourism knowledge network, its weaknesses and strengths, which can be used to make policies to have a more efficient and innovative destination. In addition, this research provides a model for future research of how to explore and analyze the inter-organizational transfer of knowledge within a tourism destination. Highlights: The knowledge network of Western Australian tourism has low connectivity and is highly centralized around public bodies. The destination has a highly clustered and hierarchical structure. Tourism actors tend to create regional clusters. The knowledge network of Western Australian tourism has similar topological characteristics to its hyperlink network. The network has a few boundary spanning actors who connect the network to the external sources of knowledge.